Critical Thinking in Nursing Education and Nursing practice - Kachapati, Anuja; Ghimire, Sulochana (Journal of Universal College of Medical Sciences, 2019)
Critical thinking is an essential component to competent nursing practice. Although critical thinking has been widely studied among student nurses.Nursing education consists of the theoretical and practical training provided to nurses with the purpose to prepare them for their duties as nursing care professionals. Nurse educators are under pressure to show critical thinking as a program outcome. Many different strategies have been suggested for developing critical thinking among nursing students. It is easy to believe these strategies increase critical thinking, but not all have actually been measured for reliability or validity. Based on an exhaustive literature search, the author attempted to identify teaching strategies that are being used to increase critical thinking and how effective those strategies have been.